Analysis of Income from Pineapple Intercropping Farming in Pasiang Village, Polewali Mandar Regency - Mardin; Ansyar; Hamsah (Program Studi Agribisnis Universitas Muhammadiyah Sinjai, 2025)
This study aims to analyze the income of pineapple-cocoa intercropping farming in Pasiang Village, Matakali District. The method used is a quantitative method with purposive sampling, and the data used are primary and secondary data that will be analyzed using income analysis by calculating total income and total costs. The results of the study indicate that the pineapple intercropping business in Pasiang Village is profitable with an income of Rp64,832,456.00/hectare/year. This income is influenced by the fairly high selling price and relatively low production costs. The pineapple-cocoa intercropping planting pattern also allows farmers to utilize land optimally and increase income. This study shows that pineapple farming can provide quite a large income for farmers in Pasiang Village.